Maqaṣid Al-Syariʿah sebagai Kerangka Evaluatif untuk Platform Crowdfunding - Hayatul Millah; Sirajul Arifin; Maula Nasrifah (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This study aims to develop an evaluative framework based on maqāṣid al-syarī‘ah for sharia crowdfunding platforms within social financing in Indonesia. The study employs a qualitative approach using a library research design, drawing on academic literature, regulations, and documents from the Islamic fintech industry. Data analysis is conducted using thematic analysis. The findings present a maqāṣid al-syarī‘ah evaluative framework consisting of three dimensions: (1) the value dimension (core maqāṣid), covering protection of religion, life, intellect, lineage, and wealth through indicators of sharia compliance, social impact, risk literacy, benefit sustainability, and fund protection; (2) the process dimension, including information transparency, sharia governance, risk mitigation, and documented fund flow; and (3) the impact dimension, measured by program sustainability, beneficiary welfare improvement, and economic empowerment. This study confirms that a maqāṣid-based approach can bridge the gap between formal compliance and socio-economic objectives in Islamic fintech. The framework is expected to serve as a foundation for developing more comprehensive and measurable evaluation standards for sharia crowdfunding. Abstrak. Penelitian ini bertujuan mengembangkan kerangka evaluatif berbasis maqāṣid al-syarī‘ah untuk platform crowdfunding syariah dalam pembiayaan sosial di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi pustaka yang bersumber dari literatur akademik, regulasi, dan dokumen industri fintech syariah. Analisis data dilakukan melalui analisis tematik. Hasil penelitian menunjukkan kerangka evaluatif maqāṣid al-syarī‘ah yang terdiri dari tiga dimensi: (1) dimensi nilai (maqāṣid inti) mencakup perlindungan agama, jiwa, akal, keturunan, dan harta melalui indikator kepatuhan syariah, dampak sosial, literasi risiko, keberlanjutan manfaat, dan perlindungan dana; (2) dimensi proses meliputi transparansi informasi, tata kelola syariah, mitigasi risiko, dan dokumentasi alur dana; serta (3) dimensi dampak yang diukur melalui keberlanjutan program, kesejahteraan penerima manfaat, dan pemberdayaan ekonomi. Kajian ini menegaskan bahwa pendekatan berbasis maqāṣid dapat menjembatani kesenjangan antara kepatuhan formal dan tujuan sosial-ekonomi dalam fintech syariah. Kerangka ini diharapkan menjadi dasar pengembangan standar evaluasi crowdfunding syariah yang lebih komprehensif.